Understanding quantum nothingness thanks to non-classical logics: The Relevance of Free Logic - Maldonado, Carlos Eduardo (2026)
Since Dirac’s paper from 1930 on the theory of electrons and protons, the question about nothingness has pervaded the right conception of reality at large in the framework of physics. Quantum Mechanics (QM) both allows and demands, at the same time, a highly counterintuitive take on the universe and the world. However, science at large remains cautious about the issue of nothingness. Apparently a referential and objectivistic view of the universe and things is preferred. This paper argues in favor of nothingness based on non-classical logics (NCLs) in general, and free logic, in particular. The crux of the issue is about thinking without presuppositions, or also, thinking about phenomena, systems and behaviors free of existence and, moreover, of reference.